Kései kaszálású széna emészthetősége és takarmányozási értéke - Magyar, Enikő Ilona; Resch, Reinhard; Szemán, László; Warner, Daniel (Gyepgazdálkodási Közlemények, 2021)
Nutritive value of a fodder from extensive established pasture was tested. The nutrient content was measured by the Wendeeanalysis and by in vitro ruminant digestibility method. Results of former experiments showed that the nutritive value of an extensive established pasture in the case of late outdoor growing is low. In our results the highest crude protein content was in the year 2002, while in 2003 can be observed a steep decline, which showed in 2004 further decrease. The crude protein values were the highest in case of middle seed norm. The nutritive values of these pastures provide just supply for the demand and it was declined due to the negative N-balance in the rumen. Our results showed that the samples from the year of establishment could possibly be used for preserved feed (6.01 MJ NE l kg-1). The crop from all other years and sowing times did not reach a value of 5.00 MJ NE l kg-1, but approach a level of 4.4 to 4.5 MJ NE l kg-1, thus they would not be suitable for preserved feed. It can be recommended that this late season crop should rather be used for grazing of livestock than as preserved feed.